2012
DOI: 10.1038/onc.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 coordinates peroxisome proliferator activated receptor gamma (PPARG) epigenetic silencing and mediates colorectal cancer progression

Abstract: Peroxisome proliferator-activated receptor gamma (PPARG) inactivation has been identified as an important step in colorectal cancer (CRC) progression, although the events involved have been partially clarified. UHRF1 is emerging as a cofactor that coordinates the epigenetic silencing of tumor suppressor genes, but its role in CRC remains elusive. Here, we report that UHRF1 negatively regulates PPARG and is associated with a higher proliferative, clonogenic and migration potential. Consistently, UHRF1 ectopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…In addition, it stimulates E-cadherin gene transcription, further supporting the anti-metastatic activity of this compound [8]. These results are consistent with the data from literature disclosing for PPARc a protective role in in vitro and in vivo colorectal cancer (CRC) models [9][10][11][12][13]. In the gastrointestinal tract, in fact, PPARc impairs cellular proliferation, stimulates differentiation and induces apoptosis [14].…”
Section: Introductionsupporting
confidence: 85%
“…In addition, it stimulates E-cadherin gene transcription, further supporting the anti-metastatic activity of this compound [8]. These results are consistent with the data from literature disclosing for PPARc a protective role in in vitro and in vivo colorectal cancer (CRC) models [9][10][11][12][13]. In the gastrointestinal tract, in fact, PPARc impairs cellular proliferation, stimulates differentiation and induces apoptosis [14].…”
Section: Introductionsupporting
confidence: 85%
“…62 Similarly, alterations in the methylation of peroxisome proliferatoractivated receptor (PPARγ) due to UHRF1-mediated DNMT3b recruitment on its promoter region resulted in progression of colorectal cancer. 63 In bladder cancer cells, UHRF1 suppressed regulator of G-protein signaling 2 (RGS2) gene expression via promoter hypermethylation resulting in cellular proliferation. 64 Role of UHRF1 in carcinogenesis was also supported by the observation that its downregulation in MKN45 Catalyzes di-/tri-methylation of H3 at lysine 9 which represses the transcription of its target genes Kim et al 1 …”
Section: Uhrf1-mediated Silencing Of Tumor Suppressor Genesmentioning
confidence: 99%
“…Recently UHRF1 overexpression has been linked to tumor progression and poor prognosis in prostate cancer and colorectal cancer (37,38). UHRF1 function in heterochromatin formation and inheritance of genomic DNA methylation patterns has long been implicated as its major oncogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated correlation of UHRF1 overexpression with tumor growth and aggressiveness and poor prognosis in prostate cancer and colorectal cancer (37,38). The oncogenic role of UHRF1 has long been implicated through epigenetic regulation, however recent indication of coexistence of UHRF1 in the same multi-protein complex with the TIP60 acetyltransferase (16,17) that modulates p53-dependent growth arrest and apoptosis leads to the attractive hypothesis that UHRF1 may be linked to the TIP60-p53 interplay and modulate the p53-dependent damage response pathway.…”
Section: Uhrf1 Interacts With Tip60 Both In Vitro and In Vivo-mentioning
confidence: 99%